Rating: New Approach - Brusov, P.N.; Filatova, T.V.; Orekhova, N.P.; Kulik, V.L. (Journal of Reviews on Global Economics, 2018)
The paper suggests a new approach to rating methodology, key factors of which are: 1) The adequate use of discounting of financial flows virtually not used in existing rating methodologies, 2) The incorporation of rating parameters (financial "ratios") into the modern theory of capital structure (Brusov-Filatova-Orekhova (BFO) theory) (Brusov P, Filatova T, Orehova N, Eskindarov M, 2015) (for beginning into its perpetuity limit). This on the one hand allows use the powerful tools of this theory in the rating, and on the other hand it ensures the correct discount rates when discounting of financial flows. We discuss also the interplay between rating ratios and leverage level which can be quite important in rating. All these create a new base for rating methodologies.